Factor Structure and Psychometric Properties of the Stressor Scale in Inclusive Education in Nursery School Teachers of Children With Special Needs in Japan: The Relationship Between Assertiveness and Stress - Shiratori, Mami; Kojima, Michio (Frontiers in Education, 2022)
Children with disabilities having special needs are increasing in Japan, placing a heavy burden on childcare workers and causing burnout. Based on the above background, this study developed a stressor scale to assess stress in childcare workers’ caring for children with special needs and assessed their degree of assertiveness, which affects their stress. The stressor scale was composed of 5 subscales consisting of 21 items. Cronbach’s coefficient alpha was .83~.93; the scale had good internal consistency and demonstrated construct validity. Moreover, a negative correlation was indicated between the assertiveness scores and “insufficient self-expertise,” a subscale of the stressor scale. The above results suggest that improvements in childcare workers’ expertise might reduce their stressors.